BASIS SIMETRIK DI RUANG BARISAN ORLICZ - , ANDINA IVANA TRIANDANI; , Dr. Supama, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
On this thesis we discuss about symmetric bases on Orlicz sequence spaces. The discussion covers some properties of Orlicz function, some properties on Orlicz sequence spaces, Orlicz sequence spaces that separable, some properties of unconditional bases on Banach spaces, some properties of symmetric bases on Banach spaces, relationship between unconditional bases and symmetric bases on Banach spaces, condition that impact uniqueness of symmetric bases on Orlicz sequence spaces and Orlicz sequence spaces that have two non equivalent symmetric bases.